Outcomes of GDD Implantation in NVG Patients at Cipto Mangunkusumo Hospital: A 3-Year Study - Sieman, Andrew John Widya; Oktariana, Virna Dwi (Majalah Oftalmologi Indonesia, 2025)
Introduction: Neovascular glaucoma is a challenging type of glaucoma to manage, due to its progressive nature. Achieving good intraocular pressure (IOP) in neovascular glaucoma cases often requires the aid of filtering surgery, preferably with a glaucoma implant/drainage device. This study aims to evaluate the outcomes of glaucoma drainage device (GDD) implantation for neovascular glaucoma patients in Cipto Mangunkusumo Hospital.   Methods: A total of 77 eyes with neovascular glaucoma were included in this study, which underwent GDD implantation in Cipto Mangunkusumo Hospital between 2020 to 2022. Baseline data include age, gender, laterality, implant type used, underlying ocular condition, systemic comorbid, visual acuity (VA), IOP, and prescribed glaucoma medications. The postoperative VA and IOP were measured at 1 day, 1 week, 1 month, 3 months, 6 months, 1 year, and 18 months or above. Complications and additional surgical interventions were noted. Success criteria based on the IOP and amount of glaucoma medications were evaluated at least 6 months postoperatively.   Results: The mean IOP at baseline was 45.91 ± 13.9 mmHg with 3.42 ± 0.77 glaucoma medications. At 6 months postoperative, mean IOP was decreased to 13.84 ± 8.6 mmHg with 1.21 ± 1.18 glaucoma medications. At 6 months follow-up, 32.0% patients achieved complete success and 48.0% patients achieved qualified success. At 1 year postoperative, the Kaplan-Meier analysis for GDD success in neovascular glaucoma cases was estimated to be 79.2%.   Conclusion: GDD implantation is an effective surgical option in treating neovascular glaucoma cases.